Lovetown. Kilka uwag o angielskim tłumaczeniu Lubiewa - Szymił, Aleksandra (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The article is an analysis of the English translation of Michał Witkowski’s Lubiewo, the translation first published in 2010 as Lovetown. The discussion focuses on the level of difficulty facing the translator, Bill Martin, in the context of numerous intertextual references in Lubiewo, the problem of memory and post-dependency. It is also an attempt at inquiry into the influence of translator’s decisions on the reception of the novel abroad. In particular, the question of translation of the aesthetic of bent and camp in the text, which is visible in theatric quality of language, use of emotionally marked expressions, hyperboles, sexual undertones, sexual language proper, language games, gay slang etc.